Re-defining Silence in Unvoiced Dialogues in Storying-play: The Sound of Affects - Li, Alison M-C; Gaffney, Janet S; Sansom, Adrienne N; Matapo, Jacoba (Journal of Childhood, Education and Society, 2023)
This article chronicles three stories selected from a post-intentional phenomenological study conducted by the first author. The authors aim to investigate affective connections in children’s silent play by addressing three research questions:  (a) How do children engage in dialogue with the teacher, their peers, and the material environment without words? (b) What emotions are produced in silent play? and (c) What changes in children’s affective connections occur through silence? We drew on the notion of intentionality in post-intentional phenomenology to illuminate meanings of the phenomenon for individuals about what they felt and experienced. With a focus on intentionality, we delved into the ways children meaningfully communicated with others and connected to the environment in their unspeaking moments. We also took on a posthuman notion of intra-actions to rethink silence as an inaudible yet sensible sound communicated between children and things. The prior studies showed that children’s silence was a mode of expression. Through storying the silent play-stories, we offered two alternative meanings of silence––intra-active communication with people and things and inaudible inner wellbeing, in addition to a mode of nonverbal expression as identified in prior studies. The findings are significant in enriching and renewing our understanding of children’s silence in inclusive ECE environments. Silence is re-defined as a mode of embodied communication and affective connections. This article invites researchers and educators to genuinely “listen” to children’s stories, even in silent play.
Keywords: silence; affects; storying; Play; early childhood education